Sub-chronic hepatotoxicity test of Plantago mayor L. extract - Eman Sutrisna; Setia Wati; Farissa Utami; Rahayu Nurmalia Fauziah; Dara AisyahRahayu Abdurrachman; Ika Murti Harini; Thianti Silviningrum (Universitas Jenderal Soedirman, 2019)
The aim of this study was to examine hepatotoxicity of Plantago mayor L. extract on rat by using effective dosage. By experimental study and post test only with control group design. 15 rats (Rattus norvegicus) were divided in to 3 group. Group A as a natural control was given aquades. Group B and C were given extract of Plantago major L. 50mg, and 100mg/200g BW rat/day per oral. Liver function was determined with measurement of Aspartate aminotransferase (AST) level, Alanine aminotransferase (ALT), total bilirubin, and histopathological feature of liver. Blood sampling and Liver organ were taken after 28 days of intervention. The average of AST levels, ALT and total bilirubin among groups A, B and C were AST levels (145.40±52.92, 129.00±34.89, and 115.60±13.24 U/l), ALT (76.40±18.87, 83.20±18.71, and 61.00±8.45 U/l) and total bilirubin (0.56±0.03, 0.77±0.22, and 0.58±0.08 mg/dL). Statistical analysis showed that there were not significantly differences of AST levels (p=0,63; CI95%), ALT (p=0,47; CI95%) and total bilirubin (p=0,0,09; CI95%) between the groups. In histopathological features, the average Scheuer score between groups A, B and C is 1.79 ± 0.74, 3.30 ± 0.66 and 2.84 ± 0.77. There is a significant difference in Scheuer scores between the groups (p=0,005; CI95%) that show that there is a difference in the effect of giving extract of Plantago major L. to hepatocyte cells leading to a piecemeal necrosis. This study can be concluded that in effective dosage, Plantago major L. extract able to induce hepatocytes injury although it cannot cause liver disfunction yet.